ECONOMIC CIVIL LAW: CONSUMER PROTECTION IN DIGITAL TRANSACTIONS AND NEW LEGAL CHALLENGES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study analyses consumer protection in digital transactions through the lens of Indonesian economic civil law, focusing on the effectiveness of the synergy between Law No. 8 of 1999 on Consumer Protection (UUPK), the Law on Information and Electronic Transactions (UU ITE), Government Regulation No. 71 of 2019 on the Operation of Electronic Systems and Transactions (PP PSTE), and Law No. 27 of 2022 on Personal Data Protection (UU PDP) in addressing e-commerce disputes, marketplace liability, and personal data management, which have proven effective in theory but face implementation challenges due to low consumer literacy and a surge in complaints; simultaneously, new legal challenges such as cross-jurisdictional transactions, AI algorithmic liability, regulatory inconsistencies, and the limitations of the Civil Code regarding smart contracts demand progressive reforms in the form of digital civil codification, Online Dispute Resolution (ODR), and AI liability regulations to foster a fair and adaptive digital transaction ecosystem.